Bio-inspired redox-cycling antimicrobial film for sustained generation of reactive oxygen species. (April 2018) - Liu, Huan; Qu, Xue; Kim, Eunkyoung; Lei, Miao; Dai, Kai; Tan, Xiaoli; Xu, Miao; Li, Jinyang; Liu, Yangping; Shi, Xiaowen; Li, Peng; Payne, Gregory F.; et al.
Abstract: Open wounds and burns are prone to infection and there remains considerable interest in developing safe and effective mechanisms to confer antimicrobial activities to wound dressings. We report a biomimetic wound dressing for the in situ and sustained generation of reactive oxygen species (ROS). Specifically, we fabricate a catechol-modified chitosan film that mimics features of the melanin capsule generated during an insect immune response to infection. We use an electrochemical reverse engineering approach to demonstrate that this catechol-chitosan film possesses redox-activities and can be repeatedly oxidized and reduced. In vitro tests demonstrate that this film catalyzes the transfer of electrons from physiological reductant ascorbate to O2 for sustained ROS generation, and confers ascorbate-dependent antimicrobial activities. In vivo antimicrobial experiment with a rat subcutaneous model indicates the catechol-chitosan film at reduced state inhibits the bacterial growth and alleviates the infection of the incisions. Open wound healing tests with a mouse model indicate that the catechol-chitosan film suppresses the bacterial population at the wound site, induces less inflammation and promotes wound healing. We envision this biomimetic approach for the sustained, localized and in situ generation of ROS could provide new opportunities for wound management by protecting against pathogen infection and potentially even enlisting ROS-mediated wound healing mechanisms. Graphical abstract: Here a bio-inspired chitosan film with grafted catechols is fabricated to catalyze the transfer of electrons from physiological reducing equivalents (e.g., ascorbate) to O2 to generate antimicrobial ROS.